Skin delivery and in vitro biological evaluation of trans-Resveratrol-Loaded solid lipid nanoparticles for skin disorder therapies - Rigon, Roberta B. [UNESP]; Fachinetti, Naiara [UNESP]; Severino, Patrícia; Santana, Maria H. A.; Chorilli, Marlus [UNESP] (MDPI, 2016)
The aim of this study was to evaluate the skin delivery and in vitro biological activity of trans-resveratrol (RES)-loaded solid lipid nanoparticles (SLNs). The SLNs were composed of stearic acid, poloxamer 407, soy phosphatidylcholine (SPC), an aqueous phase and 0.1% RES. The particle size, polydispersity index (PdI) and zeta potential were analyzed by dynamic light scattering (DLS). The SLNs were analyzed by scanning electron microscopy (SEM-FEG) and differential scanning calorimetry (DSC). In vitro RES-SLN skin permeation/retention assays were conducted, and their tyrosinase inhibitory activity was evaluated. An MTT reduction assay was performed on HaCat keratinocytes to determine in vitro cytotoxicity. The formulations had average diameter lower than 200 nm, the addition of SPC promoted increases in PdI in the RES-SLNs, but decreases PdI in the RES-free SLNs and the formulations exhibited zeta potentials smaller than -3 mV. The DSC analysis of the SLNs showed no endothermic peak attributable to RES. Microscopic analysis suggests that the materials formed had nanometric size distribution. Up to 45% of the RES permeated through the skin after 24 h. The RES-loaded SLNs were more effective than kojic acid at inhibiting tyrosinase and proved to be non-toxic in HaCat keratinocytes. The results suggest that the investigated RES-loaded SLNs have potential use in skin disorder therapies.
Keywords: Drug delivery system; Permeation; Skin disorders; Solid lipid nanoparticle; Trans-resveratrol; Tyrosinase